Vitamin E in dairy cattle feeding (review) - E. V. Tuaeva (Аграрная наука Евро-Северо-Востока)
Vitamin E (tocopherol) is a fat–soluble vitamin that has a significant effect on the growth and health of animals. Currently, 8 tocopherol isomers have been synthesized; their peculiarity lies in the different distribution of methyl groups in the chromane core. In animals, vitamin E isomers cannot convert into each other and their biological activity varies significantly. Tocopherol has a powerful antioxidant effect, protecting substances from oxidation in the body, and plays an  important role in maintaining normal metabolic processes and physiological functions. Vitamin E protects cell membranes from oxidative damage by hydrogen peroxide, helps maintain the immunomodulatory effect and increases the body's resistance to various pathogens. In addition, it performs an essential function in embryogenesis, nucleic acid metabolism, ascorbic acid biosynthesis and ensures the preservation of structural and functional characteristics of tissues. The α-tocopherol isomer has the highest biological activity. The use of α-tocopherol feed additives in the feeding of agricultural animals is presented in the form of a natural form of RRR or a synthetic form of all-rac, including all eight stereoisomers (four with the 2R configuration and four with the 2S configuration) in equal quantities. This review based on 105 publications offers a set of modern knowledge and research focused on the study of the physiological role of vitamin E in the nutrition of dairy cattle, as well as analyzes the effect of various dosages of α-tocopherol on zootechnical indicators.